Juvenile trabecular ossifying fibroma of maxilla - Rezhat Abbas; Suheel Hamid Latoo; Mohammad Shafi Dar; Owais Gowhar (Saudi Journal of Oral Sciences)
Ossifying fibroma is a rare tumor formed by abnormal cells in the ligament. There are two types of ossifying fibroma: central and peripheral. A 20-year-old female patient experienced pain and swelling on the right side of her face for one year. On intraoral examination, there was diffuse, ill-defined swelling on the right maxillary alveolus, which also involved the cheek. An excisional biopsy was carried out and histopathological findings indicated juvenile trabecular ossifying fibroma. Juvenile ossifying fibroma is a rare, benign childhood tumor known for its rapid and sporadic growth, which can cause morphologic abnormalities and, in some cases, functional deterioration. Regular and long-term follow-up is essential because of its recurrence.